Guaiacol hydrodeoxygenation as a model for lignin upgrading. Role of the support surface features on Ni-based alumina-silica catalysts. (1st May 2019) - Broglia, Francesca; Rimoldi, Luca; Meroni, Daniela; De Vecchi, Sebastiano; Morbidelli, Massimo; Ardizzone, Silvia
Highlights: Catalysts with tuneable acidity and surface area are produced by a scalable process. Increasing the amount of silica in Al2 O3 -SiO2 catalysts promotes the HDO reaction. Supports' isoelectric points give easy access to the final catalysts performance. Aromatic compounds are selectively obtained with good conversions (up to 91% in 1 h). Both regenerated and bimetallic catalysts are prepared and successfully tested. Abstract: The hydrodeoxygenation (HDO) of guaiacol is a model reaction for the upgrading of the lignin component of bio-oils, in the framework of the production of fuels from the most abundant and renewable biomass source. While Ni-based catalysts are now widely recognized as suitable catalysts for this reaction, the role of the catalyst support is far less investigated. In this work, Ni-based catalysts for the HDO reaction of guaiacol were prepared using a series of alumina-silica supports characterized by a different amount of silica (0–40%). A wide range of metal contents (0–45%) was also investigated. The reaction was performed in H2 at 50 bar and 300 °C, determining conversion, product distribution and HDO degree. Besides a notable role played by the Ni amount, the catalyst performance is markedly affected by the morphological and surface features of the support. The measured isoelectric point of the bare supports appeared to be predictive of the final performance of the relative Ni-based catalyst: the more acidic the isoelectric point, the better the overall performance of the catalyst. A regeneration treatment in mild conditions was developed to fully restore the starting surface features of the catalysts.